IMPLEMENTATION OF THE MERIT SYSTEM IN HUMAN RESOURCE MANAGEMENT IN SOUTH BURU REGENCY - Richard Solissa; Petronela Sahetapy; Stanislaus Kostka Ohoiwutun (SOSIOEDUKASI, 2026)
This study examines the implementation of the merit system in the promotion and transfer of civil servants within the Regional Secretariat of South Buru Regency, Indonesia. Despite formal regulations mandating merit-based human resource management, personnel decisions in local governments often remain vulnerable to political influence. Employing a descriptive qualitative approach, this study applies the policy implementation framework of Van Meter and Van Horn to analyze policy standards, resources, inter-organizational communication, and implementer disposition. Data were collected through in-depth interviews, observation, and document analysis involving key administrative actors. The findings reveal that although merit system standards are clearly regulated and widely acknowledged, their implementation remains largely symbolic. Limited human resource capacity, fragmented personnel data systems, weak coordination, and inconsistent commitment among implementing actors undermine substantive compliance. Political considerations continue to shape promotion and transfer decisions, negatively affecting professionalism, employee morale, and organizational effectiveness. This study contributes to public administration literature by demonstrating how political dynamics and institutional constraints hinder merit system implementation at the local level and highlights the need for stronger operational guidelines, capacity building, transparency, and accountability mechanisms.